Adrenal lipomyoma, a common incidentaloma. Presentation of two cases and review of the role of imaging - Águila Carbelo, Madyaret; Ruiz Reyes, Dionis; García Rodríguez, Diana; Esquivel Sosa, Leidelen (Salud Integral y Comunitaria, 2026)
Introduction: Adrenal incidentaloma is a condition that radiologists frequently encounter in their daily practice due to the increasing number of radiological examinations performed worldwide. An adrenal incidentaloma is defined as a mass greater than or equal to 1 cm in diameter discovered incidentally during an abdominal or thoracic imaging examination in a patient with no symptoms or signs suggestive of adrenal disease. In our setting, there has been an increase in incidentally discovered tumors, and among their causes, myelolipoma occupies a significant place in terms of frequency. Our caseload has recently been enriched with the diagnosis of myelolipomas, which are part of the incidentaloma group, despite being a benign tumor with an incidence of 0.2-0.4% in the population. Objective: The aim of this article is to demonstrate the value of imaging studies in the diagnosis of this entity through the presentation of two clinical cases. The first case is a male patient with chronic kidney disease and adrenal incidentaloma, which turned out to be a bilateral adrenal myelolipoma from a radiological point of view, unusual due to its bilateral presentation, and the second case, a 57-year-old female patient who presented with renal colic and incidentally had a unilateral adrenal myelolipoma. Conclusions: All radiologists should actively participate in the diagnosis of adrenal lesions using appropriate imaging techniques. Tomography was an effective diagnostic tool in our study.